Effects of Compudose® and Ralgro® implants and Tramisol® injectable wormer on the performance of grazing yearling steers. - Laudert, S.; Sauerwein, C.; Harris, G. (Kansas State University. Agricultural Experiment Station, 2011)
Compudose and Ralgro improved (P<.05) average daily gain 15% over non-implanted controls. No difference was observed between the two implants. Tramisol injectable wormer increased (P<.05) average daily gain 8% over non-wormed cattle.
Keywords: Beef; Implants; Performance; Steers